Allogeneic Peripheral Blood Stem Cell Transplantation in Children with Homozygous β-Thalassemia and Severe β-Thalassemia/Hemoglobin E Disease - Samart Pakakasama (2018)
To determine the outcome of children with homozygous β-thalassemia (β/β) and severe β-thalassemia/hemoglobin E disease (β/E) who underwent allogeneic peripheral blood stem cell transplantation (PBSCT). The authors conducted a cohort study of allogeneic PBSCT in β/β and β/E patients who had 6/6 or 5/6 HLA-matched sibling donors. All patients received a conditioning regimen including busulfan and cyclophosphamide, except one who received busulfan and cyclophosphamide plus antithymocyte globulin. Graft-versus-host disease (GVHD) prophylaxis consisted of cyclosporine A and methotrexate for eight patients and cyclosporine and mycophenolate mofetil for one patient. Donors received G-CSF for 4 days before leukapheresis collections. There were five β/β and four β/E patients in this study. The median age was 9 years (range 1.5-10 years). The median CD34+ cell count was 7. 4 × 106 cells/kg recipient body weight. All patients achieved neutrophil and platelet engraftment with a median time of 15 days and 21 days respectively. Acute GVHD grade 2 to 4 appeared in four patients (grade 2, n = 3; grade 4, n = 1). Three patients developed chronic GVHD (limited, n = 2; extensive, n = 1). All patients were alive with a median follow-up time of 23 months (range 7-52 months). Neither graft failure nor graft rejection was observed. Allogeneic PBSCT is feasible for children with β/β and β/E, although the incidence of GVHD was apparently high compared with bone marrow transplant study in Thais.